Blood on the Tongue: Reading Abjection in Nationalist Blood Libels From Nazi Germany to Hamas and the British National Party - Damon T. Berry (Journal of Hate Studies, 2012)
The blood libel is usually known as the Medieval European legend about Jews killing Christians to consume their blood or otherwise use it in rituals. However, in this paper I explore more recent instances of the blood libel that have emerged in nationalist contexts. What I call the nationalist blood libel is more overtly politicized than its predecessors, as there is a relationship between the accusatory portrayals of groups signified as alien and what Arjun Appadurai in Fear of Small Numbers (2006) called an anxiety of incompletion inherent in the modern nation-state as a result of the political discourses of majority and minority. In this article I discuss specific instances of the nationalist blood libel in a Nazi publication and in a cartoon aired in 2010 by Hamas wherein the Jew is signified as an agent of abjection; of transgression and dismemberment. I also examine an example from contemporary Britain in which the Islamist has replaced the Jew in the narrative, as this subject is imagined as an existential threat to the British people and the nation. In reading these examples through Julia Kristevas theorization of abjection, I contend that the telling of the nationalist blood libel relates personal and communal fears about pollution and dissolution, and that this fear, though fundamentally threatening to subjectivity, nevertheless works to establish it. I therefore argue that this reveals the nationalist blood libel as a folk reification mechanism that allows the segmentation of friend/enemy camps and rationalizes anxieties along lines of protectionism, and thereby mobilizes affects into political and often violent action.